Performance Analysis of Polarization Effects and Pre-Compensation Technique in WDM System - Seema (My University, 2010)
In WDM system, each laser must emit light at a different wavelength, with all the lasers’ light multiplexed together onto a single optical fiber. After being transmitted through a high-bandwidth optical fiber, the combined optical signals must be demultiplexed at the receiving end by distributing the total optical power to each output port and then requiring that each receiver selectively recover only one wavelength by using a tunable optical filter. The field of optical wave division Multiplexing has experienced explosive growth over the past few years. As the WDM have many advantages over the all multiplexing techniques. The objectives of this thesis is performance analysis of polarization effects and pre-compensating techniques in WDM system. Firstly the design, implementation and performance analysis of polarization effect in WDM system for different values of fiber length and polarization angle is presented. The comparison of polarization effect at various values of fiber length and polarization revealed that as we increase the length of the filter, the bit error rate will increase and eye opening will also decrease and the Q-Factor will be reduced. In both even and odd channels, the Q-factor is minimal for polarization angles equal to 0 or 180 degrees, i.e. when all channels have parallel polarization states; and Q has maximum at 90 degrees, i.e. when adjacent channels polarization state is orthogonal to each other. The BER has minimum value at 90 degree, i.e. when adjacent channels polarization state is orthogonal to each other. It is also observed the spectrums of even and odd channels. Secondly, the design, implementation and performance analysis of pre-compensation technique in WDM system on changing the different transmitter components in the circuit is presented. Components involve different modulator drivers like NRZ and RZ raised cosine, NRZ and RZ rectangular, Manchester and rectangular, Manchester and raised cosine. The investigations on pre-compensation technique has been carried out for 8 channels having bit rate of 10 Gbps and the performance has been evaluated in terms of eye diagrams, dispersion map and optical power map for different values of DCF and SMF length. The simulation results revealed that eye opening is maximum when NRZ rectangular modulator driver is used and is minimum when RZ Manchester modulation driver is used. Also, it has been observed that pre-compensated fiber gives better results than the uncompensated fiber. Moreover, the DCF of length 20km and SMF of length 80 km give the best results amongst all other fibers. Lastly, the design, implementation and performance analysis of DWDM system for different values of fiber length and channel spacing is presented. The comparison of DWDM at various values of channel spacing revealed that 100 GHz spacing has the lowest BER and better system performance. Hence, the higher spacing values between the input channels are recommended for long distance transmission without dispersion. It can be seen from the graphs of BER, Q-factor and eye opening that higher channel spacing gives the best performance as compared to lower channel spacing. The comparison of DWDM at various values of fiber length revealed that as we increase the length of the filter, the bit error rate will increase and the Q-Factor will be reduced. Thus, the thesis presents the performance analysis of WDM system on the basis of various factors.
Keywords: channel spacing, polarization; Fiber